Thermal performance of a solar cooker integrated vacuum-tube collector with heat pipes containing different refrigerants - Esen, M (Pergamon-Elsevier Science Ltd, 2004)
A solar cooking system using vacuum-tube collectors with heat pipes containing a refrigerant as working fluid has been fabricated, and its performance has been analysed experimentally. The experiments were conducted during clear days in July and August of 2002 in Elazig, Turkey under similar meteorological conditions for three refrigerants and water. Detailed temperature distributions and their time dependences were measured. The maximum temperature obtained in a pot containing 7 1 of edible oil was 175 degreesC. Also, the cooker was successfully used to cook several foods. The cooking processes were performed with the cooker in 27-70 min periods. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: solar cooker; vacuum-tube collector; heat pipe; refrigerant